Elevated body mass index and maintenance of cognitive function in late life: exploring underlying neural mechanisms - HSU, Chun Liang; Voss, Michelle W.; Best, John R.; Handy, Todd C.; Madden, Kenneth; Bolandzadeh, Niousha; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2015)
Background: Obesity is associated with vascular risk factors that in turn, may increase dementia risk. However, higher body mass index (BMI) in late life may be neuroprotective. The possible neural mechanisms underlying the benefit of higher BMI on cognition in older adults are largely unknown. Thus, we used functional connectivity magnetic resonance imaging (fcMRI) to examine: 1) the relationship between BMI and functional brain connectivity; and 2) the mediating role of functional brain connectivity in the association between baseline BMI and change in cognitive function over a 12-month period. Methods: We conducted a 12-month, prospective study among 66 community-dwelling older adults, aged 70 to 80 years, who were categorized as: normal weight (BMI from 18.50-24.99); overweight (BMI from 25.00-29.99); and obese (BMI ≥ 30.00). At baseline, participants performed a finger-tapping task during fMRI scanning. Relevant neural networks were initially identified through independent component analysis (ICA) and subsequently examined through seed-based functional connectivity analysis. At baseline and 12 months, we measured three executive cognitive processes: 1) response inhibition; 2) set shifting; and 3) working memory. Results: Obese individuals showed lower task-related functional connectivity during finger tapping in the default mode network (DMN) compared with their healthy weight counterparts (p<0.01). Lower task-related functional connectivity in the DMN at baseline was independently associated with better working memory performance at 12 months (p<0.02). Finally, DMN functional connectivity during finger tapping significantly mediated the relationship between baseline BMI and working memory at 12 months (indirect effect: -0.07, 95% confidence interval [-0.15,-0.02]). Conclusions: These findings suggest that functional connectivity of the DMN may an underlying mechanism by which higher BMI confers protective effects to cognition in late life.